2001
DOI: 10.1097/00007890-200108270-00023
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Attenuates the Increase in ??-Glutathione S-Transferase and Circulating Icam-1 and Vcam-1 After Reperfusion in Humans Undergoing Liver Transplantation1

Abstract: NAC attenuated the increase in alpha-glutathione S-transferase and circulating ICAM-1 and VCAM-1 after reperfusion of the donor liver, indicating possible cytoprotective effects of NAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 28 publications
2
41
0
3
Order By: Relevance
“…As we examined only systemic NO production, we cannot identify the site of origin. However, in view of other studies on expression of constitutive nitric oxide synthase in intestinal I/R and on the effects of NAC administration [24][25][26][27][28][29][30][31][32], intestinal constitutive nitric oxide synthase may be partially responsible for the systemic NO elevation, associated with the reduced intestinal injury, observed in our study. Similarly, in a rat model of intestinal transplantation, Sola et al identified a protective pathway initiated by ischemic preconditioning that involved the activation of NO synthesis [30].…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…As we examined only systemic NO production, we cannot identify the site of origin. However, in view of other studies on expression of constitutive nitric oxide synthase in intestinal I/R and on the effects of NAC administration [24][25][26][27][28][29][30][31][32], intestinal constitutive nitric oxide synthase may be partially responsible for the systemic NO elevation, associated with the reduced intestinal injury, observed in our study. Similarly, in a rat model of intestinal transplantation, Sola et al identified a protective pathway initiated by ischemic preconditioning that involved the activation of NO synthesis [30].…”
Section: Discussionsupporting
confidence: 44%
“…NAC is a precursor of glutathione a known cellular antioxidant [12]. Pivotal action of this drug relates to its ability to neutralize oxygen-derived free radicals, inhibit activation of the nuclear transcription factor NF-kB [23], and cytokines elaboration [24,25]. In addition, NAC as a sulfydryl donor contributes to regeneration of endothelium-derived relaxation factor [26] and attenuates the aggregation of neutrophils and platelets [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…NAC has been reported to decrease cell oxidative stress directly, inhibit activation of the nuclear transcription factor NF-kB, 78 suppress cytokine elaboration, 79 or indirectly restore the GSH content. 80 Our results demonstrated that NAC pretreatment had the protective effects on SiNPs-induced endothelial dysfunction by its antioxidant properties, including facilitating GSH biosynthesis, enhancing SOD activity, scavenging ROS via activating Nrf2 signaling pathway, and also by suppressing apoptosis and autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…However, NAC is a precursor of glutathione regeneration 15 , is a direct scavenger of free radicals 16 , inhibits inducible nitric oxide synthase expression 39 , and inhibits the expression of intercellular adhesion molecule 1 and vascular cell adhesion molecule 1 40 .…”
Section: Discussionmentioning
confidence: 99%